Maternal Genetic Mutations as Gestational and Early Life Influences in Producing Psychiatric Disease-Like Phenotypes in Mice - Gleason, Georgia; Zupan, Bojana; Toth, Miklos (Frontiers in Psychiatry, 2011)
Risk factors for psychiatric disorders have traditionally been classified as genetic or environmental. Risk (candidate) genes, although typically possessing small effects, represent a clear starting point to elucidate downstream cellular/molecular pathways of disease. Environmental effects, especially during development, can also lead to altered behavior and increased risk for disease. An important environmental factor is the mother, demonstrated by the negative effects elicited by maternal gestational stress and altered maternal care. These maternal effects can also have a genetic basis (e.g. maternal genetic variability and mutations). The focus of this review is “maternal genotype effects” that influence the emotional development of the offspring resulting in life-long psychiatric disease-like phenotypes. We have recently found that genetic inactivation of the serotonin1A receptor (5-HT1AR) and the fmr-1 gene (encoding the fragile X mental retardation protein) in mouse dams results in psychiatric disease-like phenotypes in their genetically unaffected offspring. 5-HT1AR deficiency in dams results in anxiety and increased stress responsiveness in their offspring. Mice with 5-HT1AR deficient dams display altered development of the hippocampus, which could be linked to their anxiety-like phenotype. Maternal inactivation of fmr-1, like its inactivation in the offspring, results in a hyperactivity-like condition and is associated with receptor alterations in the striatum. These data indicate a high sensitivity of the offspring to maternal mutations and suggest that maternal genotype effects can increase the impact of genetic risk factors in a population by increasing the risk of the genetically normal offspring as well as by enhancing the effects of offspring mutations.